Sildenafil does not Improve Exercise Capacity under Acute Hypoxia Exposure - Toro-Salinas, A. H.; Fort, N.; Torrella, J. R.; Pagès, T.; Javierre, C.; Viscor, G. (International Journal of Sports Medicine, 2016)
The increase in pulmonary arterial pressure (PAP) due to hypoxic pulmonary vasoconstriction (HPV) could be a limiting factor for physical performance during hypoxic exposure. Sildenafil has been shown to reduce PAP in situations of moderate or severe hypoxia, and consequently its role as an ergogenic aid and even a possible doping substance must be considered. We performed a double-blind crossover study to determine the effects of sildenafil on cardiovascular, respiratory and metabolic parameters in normoxia and during acute exposure to hypobaric hypoxia (4 000 m) at rest and during maximal and submaximal (60% VO2 max) exercise tests. One hour before testing started, sildenafil (100 mg) or a placebo was orally administered to 11 volunteers. In normoxic conditions, sildenafil did not affect performance. Similarly, no significant differences were found in cardiovascular and respiratory parameters in hypoxic conditions at rest or during exercise. The use of sildenafil to improve physical performance in non-acclimatized subjects is not supported by our data.
Keywords: sildenafil; doping; altitude; performance